2016
DOI: 10.4238/gmr.15028334
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interaction between ezrin and p65 in human breast cancer cells

Abstract: ABSTRACT. Our study aimed to investigate the co-localization and protein-protein interactions between ezrin and p65 in human breast cancer cells. Liquid chromatography-mass spectrometry (LCMS) was used to uncover novel protein interactions with ezrin in MDA-MB-231 cells. Endogenous co-immunoprecipitation was used to validate protein-protein interactions between ezrin and p65 in MDA-MB-231. Exogenous interactions between ezrin and p65 were validated in MDA-MB-231 cells via Flag-ezrin and HA-p65 co-transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated that knocking down ezrin and P65 expression induces tumor metastasis in different cancers [61, 62]. Furthermore, Tang et al [63] demonstrated that ezrin and P65 were physically associated with one another. We hypothesize that the interaction between ezrin and P65 is associated with the activation of the NF-κB pathway leading to breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that knocking down ezrin and P65 expression induces tumor metastasis in different cancers [61, 62]. Furthermore, Tang et al [63] demonstrated that ezrin and P65 were physically associated with one another. We hypothesize that the interaction between ezrin and P65 is associated with the activation of the NF-κB pathway leading to breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…12 Blood vessels enable the exchange of nutrient and catabolites for cancer cells and allow communication between primary and metastatic tumours. 13,14 Therefore, angiogenesis, the process of new blood vessel growth, is crucial for cancer development and is a potential target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-183 can inhibit metastasis of cancer cells by inhibiting ezrin protein in lung (15) and breast cancer (16). In addition, it can also inhibit migration of lung cancer cells by downregulating WISP2 protein or upregulating the expression of S100P protein (17).…”
Section: Discussionmentioning
confidence: 99%